Enabling real-time business intelligence : 6th International Workshop, BIRTE 2012, Held at the 38th International Conference on Very Large Databases, VLDB 2012, Istanbul, Turkey, August 27, 2012, Revised Selected Papers - Dayal, Umeshwar; Rundensteiner, Elke A.; Castellanos, Malu (Lecture Notes in Business Information Processing, 2013)
This book constitutes the thoroughly refereed conference proceedings of the 6th International Workshop on Business Intelligence for the Real-Time Enterprise, BIRTE 2012, held in Istanbul, Turkey, in August 2012, in conjunction with VLDB 2012, the International Conference on Very Large Data Bases. The BIRTE workshop series provides a forum to discuss and advance the science and engineering enabling real-time business intelligence and the novel applications that build on these foundational techniques. This volume contains 10 research papers, which have been carefully reviewed and selected from xx submissions.